Assessment of Workplace Difficulties Faced by Nurses Working in Public Sector Hospitals of Lahore: Workplace Difficulties for Nurses - Aslam, Naveeda; Mukhtar, Madiha; Masih, Sarfaraz (Pakistan Journal of Health Sciences, 2024)
Nursing is recognized as a stressful profession, with adverse effects on both personal health and professional performance. However, there is a scarcity of data on stress prevalence among nurses in developing countries like Pakistan. Objective: To assess stress prevalence and contributing factors among nurses in government hospitals, informing interventions to improve their work environment and well-being. Methods: This descriptive cross-sectional survey collected data from Mayo Hospital, Lady Atchison Hospital, and Said Mitha Hospital in Lahore. A structured questionnaire assessed demographic information and perceptions across four domains: Occupational Stress, Job Satisfaction, Workplace Violence, and Workplace Harassment. Likert scale items were analyzed using SPSS version 26.0, with logistic regression examining factors associated with job satisfaction. Results: Findings reveal significant concerns regarding occupational stress, job satisfaction, workplace violence, and harassment among nurses. While nurses express satisfaction with certain aspects of their job, including opportunities to utilize their abilities and relations between management and staff, concerns arise regarding workload, recognition, pay rates, and workplace violence and harassment. Logistic regression analysis indicates that age, educational qualifications, marital status, experience duration, and department insignificantly influence job satisfaction among nurses in public sector hospitals. Conclusions: These findings emphasize the urgent need to address the challenges faced by nurses to enhance their well-being and maintain a positive work environment conducive to high-quality patient care.